The Ghibliotheque anime movie guide - Leader, Michael; Cunningham, Jake (Producer) (Welbeck, 2022)
An accessible beginner's tour to the wildly popular world of Japanese animated cinema. Explore the fascinating world of Anime through more than 20 classic films in this new book from the authors of Ghibliotheque. The Ghibliotheque Guide to Anime gives an accessible beginner's tour to the wildly popular world of Japanese animated cinema, charting a path that takes in everything from titans of the industry like Akira, Ghost in the Shell and Your Name, to deeper cuts, hidden gems, and future classics that any newcomer to the artform must see. Just as Ghibliotheque was a gateway into the fantastical worlds of Spirited Away, My Neighbour Totoro and Princess Mononoke, this new guide provides a perfect entry point for film fans who want to expand their knowledge and appreciation of the genre. Each chapter focuses on one of the all-time greatest anime films, with director biographies, recommendations for further viewing and other trivia tidbits supplementing the core reviews and breakdowns of each movie. Combined with vibrant film stills and lush posters and portraits, authors Michael Leader and Jake Cunningham reveal the story behind each film, why it's a must-see, and give readers a welcoming guide through the exciting world of anime.